Requirements of a new communication technology for handover and the escalation of patient care: a multi-stakeholder analysis - Johnston,MJ; King,D; Arora,S; Cooper,K; Panda,NA; Gosling,R; Singh,K; Sanders,B; Cox,B; Darzi,A (Journal of Evaluation in Clinical Practice, 2014)
Rationale, aims and objectivesIn order to enable safe and efficient information transfer between health care professionals during clinical handover and escalation of care, existing communication technologies must be updated. This study aimed to provide a userinformed guide for the development of an applicationbased communication system (ABCS), tailored for use in patient handover and escalation of care.MethodsCurrent methods of interprofessional communication in health care along with information system needs for communication technology were identified through literature review. A focus group study was then conducted according to a topic guide developed by health innovation and safety researchers. Fifteen doctors and 11 nurses from three London hospitals participated in a mixture of homogeneous and heterogeneous sessions. The sessions were recorded and transcribed verbatim before being subjected to thematic analysis.ResultsSeventeen information system needs were identified from the literature review. Participants identified six themes detailing user perceptions of current communication technology, attitudes to smartphone technology and anticipated requirements of an application produced for handover and escalation of care. Participants were in favour of an ABCS over current methods and expressed enthusiasm for a system with integrated patient information and groupmessaging functions.ConclusionDespite concerns regarding confidentiality and information governance a robust guide for development and implementation of an ABCS was produced, taking input from multiple stakeholders into account. Handover and escalation of care are vital processes for patient safety and communication within these must be optimized. An ABCS for health care professionals would be a welcome innovation and may lead to improvements in patient safety.